2019
DOI: 10.17265/2162-5263/2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

How Has the Wine Sector Incorporated the Premises of Circular Economy?

Abstract: Much has been done in the wine production sector to promote sustainable development. Given its relevance in the economy and in society, it is fundamental to align its activities with the optimal use of resources and the regeneration and restoration of the natural system in agreement with the premises set by the Circular Economy (CE). The main interest of this work was, through a systematic literature review, to identify in the revised studies how the wine sector has incorporated the premises of CE in its activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The concept of circular economy is not yet claimed as incorporated in a lot of studies while being mentioned as a vital topic for future research. In some cases, it was confirmed that, even though the plant did not include in policies a definition of circular economy, the concepts are, in some way, present, particularly with the concern about reducing waste disposal through treatment and recovery, making the best use of resources at all stages of the chain process, and the need to rethink and redesign current practices with sustainability in mind [62].…”
Section: Analysis Of the Experience Of Applying The Circular Bioecono...mentioning
confidence: 99%
“…The concept of circular economy is not yet claimed as incorporated in a lot of studies while being mentioned as a vital topic for future research. In some cases, it was confirmed that, even though the plant did not include in policies a definition of circular economy, the concepts are, in some way, present, particularly with the concern about reducing waste disposal through treatment and recovery, making the best use of resources at all stages of the chain process, and the need to rethink and redesign current practices with sustainability in mind [62].…”
Section: Analysis Of the Experience Of Applying The Circular Bioecono...mentioning
confidence: 99%
“…Likewise, these practices have a high strategic component, given their capacity to meet the environmental needs of the different stakeholders (Camilleri, 2020). Therefore, given the ability of CEPs to improve recycling, reduction and reuse of materials and to meet the environmental demands of stakeholders, these practices can lead to increased GP of wineries (Berardi and Dias, 2019).…”
Section: Wine Tourism and Green Performance: A Perfect Matchmentioning
confidence: 99%
“…The limit of this treatment is associated with the high cost required to recover the products. In addition, publications dealing with the recovery of matter from wine lees by means of biotechnological treatments are limited [12]. There is great interest in biorefinery development focused on a complete by-product treatment, and Waste 2023, 1 an innovative approach could be the application of wine lees as a substrate for microalgal cultivation.…”
Section: Introductionmentioning
confidence: 99%